Bridging the gap between research evidence and its implementation in public health practice: case studies of embedded research model - Abisope Akintola; Dorothy Newbury-Birch; Stephanie Kilinc (BMC, 2024)
Abstract Aim To investigate the potential of embedded research in bridging the gap between research evidence and its implementation in public health practice. Methods Using a case study methodology, semi-structured interviews were conducted with 4 embedded researchers, 9 public health practitioners, and 4 other stakeholders (2 teachers and 2 students) across four case study sites. Sites and individuals were purposively selected. Sites included two local authorities, one secondary school, and one sports organisation. Thematic data analysis was adopted to analyse the qualitative data. Results Four themes were identified: (1) building and maintaining relationships, (2) working with stakeholders, (3) informing practice, and (4) critical reflection. Conclusions Embedded researchers build and maintain relationships with practitioners and other stakeholders to produce research. Evidence from the co-produced research informs future practice and research to improve service and delivery rendered to the public. Thus, embedded researchers use their role to bridge the research evidence - implementation gap in public health practice.